RESEARCH OF ELECTRICAL PARAMETERS OF START-UP PROCESS OF DIESEL ENGINES - Caban, Jacek (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2015)
During the engine start-up occurs the number of negative phenomena, which have an impact on the engine condition, its electrical equipment and the natural environment in which it is used. The starting process of the diesel engine is affected by number of factors such as: technical condition of the start-up engine unit, engine technical condition, the level of charged battery, the features of grease, engine immobilization time, engine temperature, etc. Mechanical energy needed to initiate the diesel engine start-up is supplied by electric starter motor by means of engine crankshaft. Knowledge concerning the work parameters of electrical starter during the start-up of diesel engine may be crucial not only for the user of the engine (driver of the vehicle), but above all for designers of modern diesel engine start-up units and maintenance staff. The article presents the results of electrical parameters of start-up of single cylinder diesel engine.